THE EFFECT OF IJARAH ACCOUNTING UNDERSTANDING ON IMPROVING THE FINANCIAL PERFORMANCE OF RENTAL SERVICE BUSINESS ACTORS IN BONE REGENCY - Nur Fadillah; Nikmah Marzuki (Islamic Economic and Business Journal, 2026)
This research aims to examine the impact of understanding ijarah accounting on the financial performance of rental business owners in Bone Regency. The study applies a quantitative approach utilizing a survey method. Primary data was gathered by distributing questionnaires to 96 participants and subsequently analyzed through simple linear regression. The empirical findings reveal that a comprehension of ijarah accounting positively and significantly affects the financial performance of rental businesses. Consequently, a higher level of understanding leads to more effective financial management. Therefore, knowledge of ijarah accounting serves as a crucial element in boosting the financial outcomes of rental service enterprises.